Uterine arteriovenous malformation as a non-frequent cause of abnormal uterine hemorrhage - Paredes, Rommel Omar Lacunza (2013)
The case of a patient with abnormal uterine bleeding due to acquired uterine arteriovenous malformation related to dilatation and curettage for abortion in previous months is reported. Diagnosis was done by ultrasound Doppler and Doppler 3D reconstruction. Expectant treatment and contraceptives solved the problem. Keywords: Abnormal uterine hemorrhage, uterine arteriovenous malformation, abortion.